Pengaruh Faktor Produksi Terhadap Pendapatan Usahatani Tomat di Desa Nian Kabupaten Timor Tengah Utara (Studi Kasus Kelompok Tani Oemanas Pada Masa Adaptasi Kebiasaan Baru) - Joka, Umbu (MuJAgri: Musamus Journal of Agribusiness, 2022)
The reason for this examination is to recognize the overall depiction of tomato cultivating, to distinguish the measure of pay from tomato cultivating, to recognize the effect of land region capital and work yield on the pay of tomato cultivating. The information assortment conspire utilized an enumeration cycle of up to 20 people. Information was gotten by interviews utilizing polls to respondents. Information was gotten by interviews utilizing surveys to respondents. The logical methodology utilized is an elucidating subjective examination and a different straight relapse investigation. The aftereffects of the examination show that the grouping of tomato cultivating in Nian Town includes the phases of land handling, planting, transplantation, planting, water system, weaving, preparation, Pruning, tying, post-collect preparing and moving. The normal creation procured by tomato ranchers is Rp 10.507.087,- . The real pay of tomato ranchers. In the interim, based on mostly handled information, the variable capital (X1) and land territory (X2) which had a significant effect at the degree of 0.05 (5%) and didn't have a genuine impact were variable workforce (X3).